2019
DOI: 10.29252/joge.4.1.45
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Healthy Lifestyle Multimedia Education on Elderly Life Promotion

Abstract: Introduction: Elderly health is one of the most important health issues in most societies that can be prevented by elderly problems through health care education. The purpose of this study was to determine the effect of multimedia education on promoting healthy lifestyle of the elderly in Tehran. Method: This clinical trial study was performed on two groups of thirty elderly people with mean age (63.41 6 6.88) who were members of the elderly focal points of Tehran neighborhoods with moderate to poor lifestyle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mean and standard deviation of the healthy lifestyle, self-esteem, and subjective vitality. Movahedi et al[64], and Abbasi et al[65] showed similar results. According to the results, the older people with higher education had a healthier lifestyle.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Mean and standard deviation of the healthy lifestyle, self-esteem, and subjective vitality. Movahedi et al[64], and Abbasi et al[65] showed similar results. According to the results, the older people with higher education had a healthier lifestyle.…”
mentioning
confidence: 67%
“…Older people are a vulnerable group and face a set of agespecifc problems, which are preventable by changing their lifestyle [6] because a healthy lifestyle reduces the risk of disease and premature death [7]. Lifestyle is a combination of choices, opportunities, and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Movahedi et al (2015) used the opinions of eight experts who had expertise in the eld of lifestyle or questionnaire design to determine the validity of the questionnaire, and also to determine the face validity of the questionnaire, it was implemented on 10 patients. The Cronbach's alpha coe cient of the entire questionnaire was found to be equal to 0.76 in the study of Movahedi et al 32 .…”
Section: Mediator -Life Stylementioning
confidence: 91%
“…Moving towards old age never stops, but using preventive methods and appropriate precautions, many disabilities and problems of this period can be prevented and the aging process can be delayed 6 . The best way to empower the elderly and prevent their problems is to select a healthy lifestyle 7 . This, while preventing chronic diseases, leads to the independence and autonomy of the elderly, as well as greater participation in social activities 8 .…”
Section: Introductionmentioning
confidence: 99%